MONITORING OF PARTICLE ENVIRONMENTAL POLLUTION AND FUNGAL ISOLATIONS DURING HOSPITAL BUILDING-WORK ACTIVITIES IN A HEMATOLOGY WARD. - Fabio Pattavina; Daniele Ignazio La Milia; Sara Vincenti; Barbara Fiori; Riccardo Torelli; Malgorzata Wachocka; Umberto Moscato; Simona Sica; Walter Ricciardi; Patrizia Laurenti (Mediterranean Journal of Hematology and Infectious Diseases)
Building-work activities could cause dust contamination and dissemination of fungal spores. Significant relationship was found between building-work activities and the incidence of invasive aspergillosis, in highly immunocompromised patients.